Answer:
YG you and I don't know what to do with it when I get home from work and cheese for dinner and cheese for dinner yet lol I don't know what to do with it yyyyyyy lol I don't know
Answer:
y=-2x+2
Step-by-step explanation:
okay?.......................
Answer:
C
Step-by-step explanation:
given:
m= -2 and (3, -1)
point-slope form: y-y1= m(x-x1)
y - (-1) = -2(x-3)
y + 1 = -2(x-3)
Question:
Yuet solved the equation
for a.
Her steps are shown below.
1. Subtract 2b: ![6a = 12 - 2b](https://tex.z-dn.net/?f=6a%20%3D%2012%20-%202b)
2. Divide by 6: ![a = 2 - \frac{b}{3}](https://tex.z-dn.net/?f=a%20%3D%202%20-%20%5Cfrac%7Bb%7D%7B3%7D)
Answer:
In step 1 she needed to add 2b to both sides of the equation.
Step-by-step explanation:
Given:
The above steps shows how Yuet solved an equation
Required:
True statement about Yuet's work
The implication of the statement is to state what Yuet should have done instead of what she did.
In step 1, she subtracted 2b from both sides of the equation; this is wrong.
Instead of subtracting, she ought to add 2b to both sides of the equation.
The correct steps and result is as follows:
1. Add 2b: ![6a = 12 + 2b](https://tex.z-dn.net/?f=6a%20%3D%2012%20%2B%202b)
2. Divide by 6: ![a = 2 + \frac{b}{3}](https://tex.z-dn.net/?f=a%20%3D%202%20%2B%20%5Cfrac%7Bb%7D%7B3%7D)
Hence, we can conclude that in step 1 she needed to add 2b to both sides of the equation.